Regulatory issues concerning the promotion of media literacy - Nagy, Krisztina (AoIR Selected Papers of Internet Research, 2016)
The convergent media space necessitates new regulatory approaches and solutions because as a result of the explosive growth in the amount and types of media contents, and the appearance of contents created by users and the globalisation of the media universe, the previous control-based approach towards the media universe has become outdated. *The new regulatory regime requires autonomous users who strive to keep themselves informed about the complex new digital environment and are also capable of managing the risks that they are burdened with*. Media literacy presumes knowledge and skills that result in responsible and autonomous decision-making, as well as the maximisation of opportunities that arise out of the informational environment and the minimisation of the corresponding risks. The objective of promoting media literacy is no longer just an education policy issue but has also emerged as a general public policy challenge that necessitates a redefinition of the state's role.The research seeks *an answer to the question of what responsibilities the state must assume in the context of promoting an informed and responsible use of the new media environment, especially the internet*. What are the institutional solutions that can provide the basis for promoting user awareness (protection, responsibility, information and participation)? The paper reviews and schematically arranges the instruments necessary for promoting the knowledge and skills that provide the basis for responsible and informed media/internet usage. It will further define the regulatory starting points and instruments aimed at promoting media literacy.